Pemanfaatan Tepung Biji Nangka (Artocarpus heterophyllus) dan Tepung Singkong (Manihot esculenta) Dengan Penambahan Pigmen Klorofil Pada Sayuran Sebagai Sumber Antioksidan Beras Analog - Silvia Khilmi; Damat Damat; Elfi Anis Saati (Universitas Muhammadiyah Malang, 2020)
Jackfruit seeds have high carbohydrate and protein, which is around 56.21% and 12.19%. Substitution with cassava starch which has amylose and amylopectin can help analog rice characteristics. The addition of natural dyes such as chlorophyll is also needed in the diversification of analog rice food as a source of antioxidants. The purpose of this study was to find out the diversification of jackfruit seed processing through the use of jackfruit seed flour and cassava flour substitution into analog rice, determine the effect of adding extracts to different vegetables on the physicochemical and organoleptic properties of analog rice, knowing the presence of chlorophyll and antioxidant content in analog rice substitution jackfruit seed flour and cassava flour. This study uses Nested design / nested design. Nest/parent namely the proportion of flour with 3 levels (10% jackfruit seed flour and 90% cassava flour, 20% jackfruit seed flour and 80% cassava flour, 30% jackfruit seed flour and 70% cassava flour) and the nest is a pigment with 4 levels (without pigments, green spinach pigments, suji leaf pigments, moringa leaf pigments). The results showed a very significant effect on water content, ash content, fat, protein, carbohydrates, antioxidants, chlorophyll, absorption, brightness, color (a-), and color (b +), redeem and organoleptic such as taste, texture, shape, and liking. Organoleptic texture has no real effect. The best treatment for T3W2 treatment is the proportion of 30% jackfruit seed flour and 70% tapioca flour with the addition of pigment from green spinach.